Wakefield excitation by sequences of relativistic electron bunches in dielectric cavity at detuning bunch repetition frequency and frequency of eigen principal mode - Balakirev, V.A.; Onishchenko, I.N.; Tolstoluzhsky, A.P. (Вопросы атомной науки и техники, 2014)
Process of wakefield excitation by short and long sequences of relativistic electron bunches with finite both longitudinal and the transverse sizes is investigated. It is shown that at the presence of detuning between the bunch repetition frequency and the frequency of excited synchronous oscillations the beating of oscillations in time is formed. The first part of the sequence of bunches loses energy on wakefield excitation resulting in wakefield amplitude growth. The second part of the sequence of bunches gains energy resulting in wakefield amplitude decrease. Thus, in the dielectric cavity the regime of relativistic electrons autoacceleration can be realized by introduction of frequency detuning. Исследован процесс возбуждения кильватерных полей в диэлектрическом резонаторе как короткой, так и длинной цепочками релятивистских электронных сгустков, имеющих конечные продольные и поперечные размеры. Показано, что при наличии расстройки между частотой следования сгустков и резонансной частотой собственного колебания формируется биение возбуждаемых колебаний. Первая половина сгустков теряет энергию на возбуждение кильватерного поля, при этом амплитуда поля растет. Вторая половина электронных сгустков в цепочке приобретает энергию от поля. Амплитуда кильватерного поля соответственно убывает. Следовательно, в диэлектрическом резонаторе путем введения расстройки может быть реализован режим автоускорения. Досліджено процес збудження кільватерних полів у діелектричному резонаторі як короткими, так і довгими ланцюжками релятивістських електронних згустків, що мають скінчені поздовжні та поперечні розміри. Показано, що при наявності розладу між частотою проходження згустків і резонансною частотою власного коливання формується биття збуджуваних коливань. Перша половина згустків втрачає енергію на збудження кільватерного поля, при цьому амплітуда поля росте. Друга половина електронних згустків у ланцюжку одержує енергію від поля. Амплітуда кільватерного поля відповідно убуває. Отже, у діелектричному резонаторі шляхом введення розладу може бути реалізовано режим автоприскорення.